Evaluation of teachers’ training and development programmes in secondary schools: Administrators’ and teachers’ perceptions - Asuquo, Michael Ekpenyong; Owan, Valentine Joseph; Ekpenyong, John Asuquo; Undie, Stephen Bepeh; Mbon, Usen Friday; Anagbogu, German Effa; Ukpong, Nse Nkereuwem; Okpa, Ovat Egbe; Dan, Felicia Agbor-Obun; Okoi, Ikpi Inyang; Otu, Bernard Diwa; Ategwu, Patrick Ogar (Nurture, 2023)
Purpose: This study evaluates staff Training and Development Programmes (TDPs) in secondary schools based on the views of administrators and teachers. The research was implemented in public secondary schools in Cross River State, Nigeria. Design/Methodology/Approach: The study adopted the survey research design with 5408 participants (administrators = 542; teachers = 4595). Four research questions guided the study. The Staff Training and Development Programmes Questionnaire (STDPQ) was used for data collection. Findings revealed essential areas of staff training and development. Findings: Various methods are employed for staff training and development. The results further showed various constraints that impeded staff TDPs in secondary schools. Conclusion: Based on the findings, it was concluded that staff in secondary schools have different training and development needs adjudged by both the principals and teachers as crucial for job enhancement. Various staff training and development methods can serve as valuable programmes to improve the current methods adopted. Research Limitations and Implications: There are various limitations in this study such as the small scope which may affect the extent to which generalizations can be made. It is suggested that future studies focus on expanding the scope to other regions and nations. Practical Implications: Despite the limitations, the study has made some advances to human capital and self-determination theories by providing findings. The findings of this study may direct the attention of curriculum planners, the government and school management to offer training and development opportunities based on the needs of teachers. Contribution to Literature: The study has contributed to the literature on staff training and development which can constitute a basis for further research in related areas.